Cost Analysis of the Use of Voriconazole, Posaconazole and Micafungin in the Primary Prophylaxis of Invasive Fungal Infections in Recipients of Allogeneic Hematopoietic Stem Cell Transplants - Santiago Grau; Carlos Solano; Carol García-Vidal; Isidro Jarque; Jon A. Barrueta; Carmen Peral; Irene Rodríguez; Darío Rubio-Rodríguez; Carlos Rubio-Terrés (Journal of Health Economics and Outcomes Research)
**Objectives:** Compare the cost of the primary prophylaxis of invasive fungal infections (IFI) with voriconazole, posaconazole, and micafungin in patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT) in hospitals of the National Health System (NHS) in Spain.